A lead to world socialism on Spain, war, fascism, imperialism - Brockway, Fenner, 1888-1988 ; Revolutionary Socialist Congress (1936 : Brussels, Belgium) ; Partido Obrero de Unificación Marxista; Gorkin, Julián, 1901- (London : International Bureau for Revolutionary Socialist Unity, 1936)
1936 SA14-030-027 36 pages : illustrations, 1 portrait ; 21 cm. 15X/2/227/1